2011
DOI: 10.1016/j.physbeh.2011.02.041
|View full text |Cite
|
Sign up to set email alerts
|

Hair cortisol levels as a retrospective marker of hypothalamic–pituitary axis activity throughout pregnancy: Comparison to salivary cortisol

Abstract: Maternal stress during pregnancy is associated with negative maternal/child outcomes. One potential biomarker of the maternal stress response is cortisol, a product of activity of the hypothalamic-pituitary-adrenal axis. This study evaluated cortisol levels in hair throughout pregnancy as a marker of total cortisol release. Cortisol levels in hair have been shown to be easily quantifiable and may be representative of total cortisol release more than single saliva or serum measures. Hair cortisol provides a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
270
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 298 publications
(294 citation statements)
references
References 37 publications
12
270
5
Order By: Relevance
“…Consequently, a loss of the substances may occur by washout effects, for example, cosmetic treatment (permanent waving, dyeing), or leaching out caused by mechanical damages of the hair structure. 43,44 The washout was also observed by several others 9,19,21,45 but not by all 46,47 groups. Manenschijn et al 46 assumed that washout of steroids results from hair sample decontamination steps before analysis.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…Consequently, a loss of the substances may occur by washout effects, for example, cosmetic treatment (permanent waving, dyeing), or leaching out caused by mechanical damages of the hair structure. 43,44 The washout was also observed by several others 9,19,21,45 but not by all 46,47 groups. Manenschijn et al 46 assumed that washout of steroids results from hair sample decontamination steps before analysis.…”
mentioning
confidence: 63%
“…[16][17][18] Various studies were concerned with the question whether this increased cortisol concentration is also detectable in hair. [19][20][21] Compared with control samples, the cortisol concentrations (measured by immunoassays) showed the highest values (40-50 pg/mg) in the proximal segments of hair samples correlated to the third trimester. Elevated cortisol concentrations were reported to be detectable up to 3 months after pregnancy.…”
Section: Introductionmentioning
confidence: 88%
“…In the past years, several laboratories have expanded hair analysis to measure long-term levels of cortisol and other steroid hormones (5,6,7,8,9,10). This has allowed researchers to investigate cortisol exposure over much longer periods of time (months to years) than previously possible with samples of blood, saliva or urine.…”
Section: Introductionmentioning
confidence: 99%
“…e Kirschbaum group used 25-50 mg in their rst publications [8] and 10-15 mg in their recent studies [10] while the Laudenslager group [3] used 50 mg.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, hair cortisol has become a topic of global interest as a biomarker of chronic stress [2]. An increasing body of evidence has shown that hair cortisol levels re ect systemic plasma levels of the hormone over time, allowing estimation of chronic stress, both psychological and physiological, as well as disorders of the hypothalamic-pituitaryadrenal axis, including Cushing syndrom and Addison's disease [2][3][4].…”
mentioning
confidence: 99%